The Models of Compounding in Neologisms - MELQONYAN, LUIZA (Bulletin of Yerevan University B: Philology, 2021)
The article presents the forms of neologisms. In neologisms, formed by means of word combinations, a larger part are connected with subordinating relations, which, in general, are considered to be contrastive combinations. As for neologisms, the most effective and prevailing forms of compounding are the following: noun + noun, verb + noun, noun + verb, adjective + noun. Coordinative combinations are not great in number; they are mainly considered to be analytical combinations and have casual value.